Evaluation of roots, root canal morphology, and bilateral symmetry of maxillary first molars in a Syrian subpopulation using cone beam computed tomography - Safaa Allawi; Helen Ayoubi; Mouhammad Al‐Tayyan; Eyad Toutangy; Yasser Alsayed Tolibah (Wiley, 2023)
Abstract Objective Successful endodontic treatments require a comprehensive knowledge of the root canal anatomy, so this study aimed to investigate the number of roots, configurations of root canals, and their bilateral symmetry of maxillary first molars in the Syrian subpopulation, and also the effect of gender on this symmetry. Materials and Methods The study sample consisted of 250 cone beam computed tomography images (140 for females; and 110 for males), including 500 maxillary first molars. Images were investigated by two endodontists. Root number and canal configuration in each root were recorded, according to Vertucci classification, by studying the image at all levels (axial, coronal, sagittal, oplique, and three‐dimensional) to assess the bilateral symmetry and its relation to gender. Statistical analysis was performed with SPSS and the χ2 test was used to compare the bilateral symmetry in males and females. Result The most common shape of the maxillary first molars was three roots (97.6%). All the roots are symmetrical by 100% in both genders. The root canal configuration was mainly Vertucci type I classification in the distobuccally (73.6%), and palatal root (98%). While the most common types in mesial root were type II (33.3%), this root showed all different types of Vertucci classifications except type VIII, and the proportion of symmetry was (37.2%) without significant difference between the gender (p = .441). Conclusion Most maxillary first molars in a Syrian population were three‐rooted with four root canals (type II), the numbers of roots achieved perfect symmetry 100%, and higher than symmetry ratios in the number of canals and canals configurations (37.2%).